An empirical model of airline fleet standardization in Brazil: Assessing the dynamic impacts of mergers with an events study. (October 2020) - Narcizo, Rodolfo R.; Oliveira, Alessandro V.M.; Dresner, Martin E.
Abstract: This paper develops an empirical model to investigate the strategic fleet management practices in the air transport industry regarding airline fleet standardization (AFS). We conduct an econometric analysis of the key drivers of AFS in Brazil and study the dynamic effects of five merger events. We find evidence of a significant drop in AFS following most of the consolidations, which is gradually reversed during the post-merger integration efforts. Additionally, except for the major full-service carrier, all other airlines had an estimated overall trend toward more intense fleet standardization over the entire period, revealing a stronger preference for seeking cost competitiveness over market opportunity when facing competition in the market. Highlights: We develop an econometric model of strategic fleet management with respect to airline fleet standardization (AFS). We study the impacts of five merger events on fleet standardization-diversification. AFS decreases after most of the consolidations but gradually increases in the post-merger integration period. The results are consistent with airline preference for seeking cost competitiveness over market opportunity .